1997
DOI: 10.3109/01674829709080698
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for anxiety about childbirth in 100 pregnant women

Abstract: The aims were to document conscious reasons for anxiety about childbirth. Pregnant women (n = 100), consecutively referred from antenatal centers to a psychosomatic outpatient clinic because of extreme fear of childbirth, were interviewed. Three subgroups are described: primiparae (n = 36), women with a normal previous delivery (n = 18) and women with a previous complicated delivery (n = 46). Anxiety over the deliver was related to lack of trust in the obstetrical staff (73%), fear of own incompetence (65%), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 11 publications
6
118
1
12
Order By: Relevance
“…It has been well demonstrated that fathers of the pregnancy, just like their female counterparts, have anxiety over delivery. 26 Both the mother and the father have appraisals, coping strategies and support resources with adjustment to parenthood, although the mechanism might differ substantially. 27 A study on the psychosocial influence on women's experience of planned ELCS showed that partner's fear mediated between maternal fear and postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well demonstrated that fathers of the pregnancy, just like their female counterparts, have anxiety over delivery. 26 Both the mother and the father have appraisals, coping strategies and support resources with adjustment to parenthood, although the mechanism might differ substantially. 27 A study on the psychosocial influence on women's experience of planned ELCS showed that partner's fear mediated between maternal fear and postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…19 Fear of loss of self-control in labour has been implicated as one of the reasons for women choosing ELCS. 20 The Chinese version of MHLC is available. 21 The scale assesses three dimensions of control namely; internal control by oneself (IHLC), control from powerful other (PHLC) and control by chance (CHLC).…”
Section: Psychometric Scalesmentioning
confidence: 99%
“…Anxious women have a predisposition towards having negative birth expectations (Heaman et al, 1992;Sjogren, 1997), which renders midwives accountable for instilling confidence through delivering effective preparatory education. Preparation for childbirth palpably influences birth satisfaction (Dannenbring et al, 1997), with engagers more confident and able to cope (Sinclair, 1999).…”
Section: (Q4) I Felt Anxious During My Labour and Birthmentioning
confidence: 99%
“…On alt boyuta sahip olan ölçeğin ters soruları yoktur. Öl-çeğin alt boyutlarından OWLS ile ilişkili olan "doğum eylemine ilişkin endişeler" (11,12,13,14,15,16,17,18,19,20 Ölçek; doğum öncesi, sırası ve sonrası bütün dönem-lerde kadınlara uygulanabilmektedir; "1: Çok endişeliydim", "2: Oldukça endişeliydim", "3: Çok endişeli değildim", "4: Hiç endişeli değildim" şeklinde puanlanmıştır. Ölçek toplam puan üzerinden değerlendi-rilmektedir (min=10, maks=40).…”
Section: Gereç Ve Yöntemlerunclassified
“…10 Sjögren, 100 gebe üzerinde yaptığı bir çalışmada, güvenilir sağlık personeli eksikliği (%73), kendisinin yetersizliği korkusu (%65), annenin, bebeğin ya da her ikisinin ölme korkusu (%55), tolere edilemeyen ağrı hissi (%44) ve kontrolünü kaybetme (%43) gibi duyguların gebelerde anksiyete sebebi olduğunu bulmuş-tur. 12 Huizink ve ark.nın çalışmasında ise gebelerin çocuk doğurmaktan, fiziksel veya zihinsel özürlü çocuk doğurmaktan ve kişisel görünümlerinin bozulmasından endişe duydukları belirlenmiştir. 13 Doğum korkusu travay süresinin uzamasına, epidural analjezi ve yardımcı tekniklerin kullanı-mının artmasına neden olmaktadır.…”
unclassified